Morphology and paleobiology of the Late Cretaceous large-sized shark Cretodus crassidens (Dixon, 1850) (Neoselachii; Lamniformes). (September 2022) - Amalfitano, Jacopo; Dalla Vecchia, Fabio Marco; Carnevale, Giorgio; Fornaciari, Eliana; Roghi, Guido; Giusberti, Luca
Abstract: The definition of the Cretaceous shark genus Cretodus Sokolov, 1965 is primarily based on isolated teeth. This genus includes five species. Among these, Cretodus houghtonorum Shimada and Everhart, 2019 is the only species based on a partially preserved skeleton. Here, the taxonomic attribution of a virtually complete skeleton of Cretodus from the Turonian of northeastern Italy is discussed, together with a few specimens from the Turonian of England. One of the latter is investigated through micropaleontological analysis to determine its stratigraphic position. The material is referred to Cretodus crassidens (Dixon, 1850 ), the diagnosis of which is emended herein. The dentition is tentatively reconstructed, exhibiting strong similarities with congeneric species, although it differs in having strong vertical folds on the main cusp labial face, a mesiodistally broad tooth aspect, weak and well-spaced 'costulae' at crown base, and a different dental formula in the number of parasymphyseal and lateral rows. Some tooth malformations are interpreted as feeding-related or senile characters. The Italian specimen suggests that Cretodus crassidens had a wide and laterally expanded mouth and head, a stout body, and attained a gigantic size. Cretodus crassidens was a moderate-speed swimming shark ecologically like the extant tiger shark Galeocerdo cuvier (Péron and Lesueur in Lesueur, 1822 ). The age estimate from vertebral-band counting suggests that the Italian individual was at least 23 years old and the growth model indicates a longevity of 64 years and a maximum attainable total length of 9–11 m. Cretodus crassidens occurs both in Boreal and Tethyan domains, implying a broad paleobiogeographic distribution and a preference toward offshore settings.